The role of Tenascin‐C and Twist1 in gastric cancer: cancer progression and prognosis. Issue 2 (30th January 2019) - Qi, Wenbo; Yang, Zhaoting; Li, Haoyue; Cui, Yan; Xuan, Yanhua
Abstract : The aim of the present study was to identify the relation between Tenascin‐C (TNC) and Twist1 and determine their clinical significance in gastric cancer (GC). We analyzed the expression of TNC and Twist1 in 159 GC samples and in 91 non‐tumor samples using immunohistochemistry. In this study, TNC expression in stromal fibroblasts of GC was remarkably higher than non‐tumor gastric lesions. The expression of TNC in GC stromal fibroblasts was significantly associated with pT stage, lymph node metastasis, distant metastasis. Twist1 expression in stromal fibroblasts of GC was remarkably higher than non‐tumor gastric lesions. Twist1 expression in the stromal fibroblasts of GC was associated with tumor size, lymph node metastasis, and clinical stage. Furthermore, TNC expression levels in GC stromal fibroblasts were positively associated with Twist1. The simultaneous expression of TNC and Twist1 was significantly higher in stromal fibroblasts of GC than in noncancerous tissues. The simultaneous expression of TNC and Twist1 in GC stromal fibroblasts was positively associated with tumor location, pT stage, lymph node metastasis and clinical stage. Moreover, patients with co‐expression of TNC and Twist1 had a poorer prognosis than either TNC or Twist1 positive in GC. Our study revealed that the simultaneous expression of TNC and Twist1 indicated the poorer prognosis of GC. Co‐targeting TNC and Twist1 confer significant clinical advantage, which offers a novel therapeutic target in GC.